Exploring The Impacts Of Cleaner Production On Manufacturing Sustainability In Malaysia - An Initial Study - Wan Mahmood, Wan Hasrulnizzam; Yusup, Mohd Zaki; Salleh, Mohd Rizal; Amat, Rafidah (Publications International Lahore, Pakistan, 2014)
The ability to adapt with the cleaner production in various dimensions of manufacturing successfully increases the sustainability in production operations. Driven by the opportunity for improvement, this study was undertaken to explore the extent to which cleaner production practice influences the level of manufacturing sustainability in the context of Malaysian industry. The findings from this initial study showed that the execution performance of this practice on a regular basis and systematic brings positive effects on all the necessary components in establishing the sustainable manufacturing namely environment, economy and competency. Emphasis on systematic environmental management practice found to encourage comprehensive actions in addressing the environmental concerns. This subsequently increases the competency in management and operation, which eventually provide benefits for financial and environmental performance. Moreover, the findings also can be used as a referral for the next research, primarily in formulating a comprehensive strategy in achieving sustainability in manufacturing, as well as enhancing the continuity of business in the future.